Legal Analysis Regarding the Responsibilities of Intermediaries in the Sale and Purchase of Land - Joharsah, Joharsah; Muhlizar, Muhlizar (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Inside practice, sell-buy that involves party seller and buyer, especially on purchases right on land, requires a party third to be on duty as an intermediary with function as a giver of information, a liaison, as well as someone acting as a recipient of power. Following the Civil Code in Article 1792, which regulates gift power of attorney, and Article 1338, paragraph (3), everything must be done in good faith. However, not all intermediaries can operate, giving trust to them with ok. Practical loss in some party Study This will describe factors from the cause of the selling process, buy right on done land through the intermediary role, and not quite enough answer party third the recipient power inside the buy right on done land. Studying this also explains the consequence law. Suppose there is a default and also in the process of settlement. The interview process is used to collect data; the informant or respondent reluctantly conducts field and literature research and a qualitative forward analysis study. From research, those are the givers of power to intermediaries for a more thorough and considerate application of various principles, especially justice for all parties.